2013
DOI: 10.14310/horm.2002.1446
|View full text |Cite
|
Sign up to set email alerts
|

Association between g.19163A>G and g.23298T>C genetic variants of the osteoprotegerin gene and bone mineral density in Chinese women

Abstract: ObJEctIVE: Osteoporosis is a serious and common health issue of considerable complexity among postmenopausal women. the osteoprotegerin gene (OPG) is considered to play an important role in the pathogenesis of osteoporosis. the objective of this study was to detect single nucleotide polymorphisms (sNPs) in the OPG gene and assess the association between bone mineral density (bMD) and sNPs in postmenopausal women. MEtHODs: bMD was measured at the lumbar spine (L2-4), neck, and total hip by dual energy X-ray abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…Previous studies have demonstrated that changes in the OPG serum level are influenced by genetic polymorphisms, including 950T/C at the rs2073617 locus, 1181 G/C at the rs2073618 locus and 1181 G/C at the rs2073618 locus ( 33 35 ). The association between genetic polymorphisms in the OPG gene and bone mineral density has been the focus of previous investigations ( 36 , 37 ). Previous studies have implicated increased bone mineral density in the etiology of IDD ( 38 , 39 ); however, few studies have focused on a direct association between OPG genetic polymorphisms and the risk of IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that changes in the OPG serum level are influenced by genetic polymorphisms, including 950T/C at the rs2073617 locus, 1181 G/C at the rs2073618 locus and 1181 G/C at the rs2073618 locus ( 33 35 ). The association between genetic polymorphisms in the OPG gene and bone mineral density has been the focus of previous investigations ( 36 , 37 ). Previous studies have implicated increased bone mineral density in the etiology of IDD ( 38 , 39 ); however, few studies have focused on a direct association between OPG genetic polymorphisms and the risk of IDD.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies show contradictory results in this regard. There are seven polymorphic sites (i.e., Ilu16Thr, Thr20Ilu, Cys87Tyr, Val104Met, Phe117Leu, Cys87Tyr, Cys65Arg) in exon 2 of the OPG gene (6,10,(15)(16)(17)(18). Four of them were mainly studied in Chinese postmenopausal women and the findings confirmed their associations with BMD (10,(15)(16)(17).…”
Section: Discussionmentioning
confidence: 68%
“…Three other sites were indicated to be related to idiopathic hyperphosphatasia phenotypes (severe to mild phenotypes), including deformities and fractures in two girls and one boy in Argentina and Turkey (6). One of these polymorphic sites (Phe117Leu), which was observed in an idiopathic hyperphosphatasia girl in Argentina, was also studied in Chinese women and claimed to be associated with BMD (18). The Cys87Tyr site, which was related to severe phenotype in an idiopathic hyperphosphatasia boy with homozygote form (Tyr/Tyr), may also be a good candidate for investigating the possible association with BMD.…”
Section: Discussionmentioning
confidence: 99%
“…The OPG gene has been verified as being involved in bone remodeling, bone mineral homeostasis, and bone matrix composition (Liu et al, 2013) neck, and total hip by DEXA. However, to date, no studies have been published that evaluate the relationship of the 1181G>C and 163A>G SNPs of the OPG gene with BMD in patients with T1DM, despite evidence that these polymorphisms are associated with a loss of bone mass (Shang et al, 2013;Song et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…As an active component of this system, therefore, polymorphisms in the OPG gene might influence bone metabolism and BMD (Wang et al, 2013;Guo et al, 2014) neck hip and total hip was determined by dual-energy X-ray absorptiometry (DEXA). Although several studies have investigated the association of OPG single nucleotide polymorphisms (SNPs) such as 163A>G, 1181G>C, 245T>G, and 950T>C with BMD and bone disorders (Feng et al, 2012;Liu et al, 2013;Wang et al, 2013;Yu et al, 2013;Guo et al, 2014) which is characterized by a decrease in BMD, the relationship between the 1181G>C and 163A>G SNPs of the OPG gene and T1DM and BMD has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%